Colors of reflection nebulae. I - Phase function effects in the Merope nebula - Witt, A. N. (The Astrophysical journal, 1985)
The subject of color differences between reflection nebulae and their illuminating stars is reexamined in the light of developments of observational techniques, permitting accurate surface-brightness photometry over an expanded spectral region from the UV to the IR. Color-color diagrams for reflection nebulae can yield useful information about the wavelength dependence of the scattering properties of nebular dust without excessive sensitivity to the specific nebular geometry or the presence of multiple scattering, resulting in considerable savings in computational efforts. As an illustration, the color-difference method was applied to existing data for the Merope nebula, covering the spectral region 1550-5500 A. Strong evidence for a monotonically changing phase function of scattering at wavelengths less than or equal to 3500 A is found. The result is interpreted in the context of a plausible geometry for the Merope environment as providing support for a bimodal size distribution of nebular dust grains.